Wiley 2016 interpretation and applications of International Financial Reporting Standards - Chaudhry, Asif, 1979-; Fuller, Craig; Coetsee, Danie; Rands, Edward; Bakker, Erwin; Merwe, Minette van der; Yeung, Paul; Varughese, Santosh; McIlwaine, Stephen; Balasubramanian, TV (Wiley, 2016)
'Wiley IFRS 2016' provides the necessary tools for understanding the IASB standards and offers practical guidance and expertise on how to use and implement them
Obsahuje rejstřík
Keywords: International Accounting Standards Board; IFRS (International Financial Reporting Standards); mezinárodní účetní standardy; hospodářské výsledky; harmonizace účetnictví; účetní výkazy; international accounting standards; economic results; harmonization of accounting; financial statements; elektronické knihy; electronic books